Makna Hewan Kucing Hitam: Analisis Semiotika Roland Barthes - Shidqi, Raihan Dhiaul; Sari, Retno Purwani (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study aims to explore the symbolic meanings of black cats through Roland Barthes' semiotic framework, focusing on three levels of meaning: denotative, connotative, and mythological. Black cats have long served as cultural symbols associated with myth, mysticism, and diverse interpretations across Indonesian and Western societies. This research applies a descriptive qualitative approach, utilizing direct observation and literature review for data collection. The findings reveal that visual elements such as black fur, eyes, and claws of cats carry layered meanings influenced by cultural values, ideologies, and community beliefs. The color black symbolizes darkness and death; cat eyes are associated with mystical realms; while cat claws are seen as omens or warnings. These symbols are shaped and interpreted through complex social and historical processes. The results highlight that even a simple object like a black cat can possess deep, culturally constructed meanings that require contextual understanding. Keywords: Semiotics, Black Cat, Denotation, Connotation, Myth